Simulation of handoff algorithm for NDN producer’s mobility - Ahmed, Muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Khalifa, Othman Omran; Alkali, Abdulkadir Hamidu; Adamu, Zainab Mohammed (Institute of Advanced Scientific Research, Inc., 2020)
Named Data networking is a novel communication scheme designed for efficient data dissemination. NDN is cantered on content management to improve on IP challenges such mobility, scalability, security and better quality of service. In this paper, producer’s mobility between two points is set-up for simulation using hard handoff technique. In this form of handoff, the carrier frequency of a connecting access gateway remains the same with the newly visited gateway of the producer (i.e intra-frequency). The mobile producer in node 3 is requesting a video content to another producer in node 4 while in a state of mobility. We considered anchorless technique of managing mobility of the nodes and simulation ensures that contents still receive routing update as they achieve handoff. These set-ups of simulation were conducted using NetSim version 12.10 software. In the results, we present video application throughput and the link throughput of link 1, link 2 and link 7 and comprehend that, efficiency and seamless mobility is realized using video application as compared to link throughout. Network and queued metrics also present more results being generated after the simulation processes. The algorithm of our inputs is tested in MATLAB and part of the coding system is build using visual studio 2015 which by default, is compatible with NetSim “binary” and “dll” folders.